Studi Kasus Analisis Defect Pada Komponen Otomotif Disertai Pemecahan Masalah Menggunakan Diagram Pareto Dan Fishbone - Agus Setiawan; Aulia Deswita; Shofiyaturrahmah Shofiyaturrahmah; Ferry Budi Firmansyah; Yudi Prastyo (JURNAL ILMIAH RESEARCH STUDENT, 2025)
The problem of defects in automotive components remains a major challenge in the manufacturing industry, as it directly impacts product quality, production process efficiency, and customer satisfaction. This research aims to analyze the most frequent types of defects in one automotive component, identify their root causes, and provide applicable improvement solutions. The study was conducted using a Quality Control Circle approach with the Pareto Diagram to prioritize defect types based on their frequency and impact, and the Fishbone Diagram to identify root causes based on the 4M+1E categories (Man, Machine, Method, Material, Environment). The results show that rust and out-of-standard defects are the most dominant, generally caused by a lack of operator understanding, unstable machine conditions, non-standard work methods, and suboptimal raw material quality and work environment. Improvement recommendations include operator training, machine repair, work method adjustments, and production environment supervision. The implementation of these solutions has proven to significantly reduce defect rates and improve product quality. The integration of Pareto and Fishbone diagrams has proven effective as an applicable quality control strategy in the automotive industry.